South Gaulish terra sigillata found in Bracara Augusta (North Portugal) - Morais, Rui (2021)
Bracara Augusta, just like other nuclear cities of the Roman world, played an important role in the inter-provincial trade as an importer and redistributor centre of nourishing and manufactured goods. Regarding the supply of Gaulish terra sigillata, apart from some fragments from Montans and a Drag. 45 form fragment from Lezoux, the productions are from La Graufesenque.